Association between −308 G/A TNF-α Polymorphism and Appendicular Skeletal Muscle Mass Index as a Marker of Sarcopenia in Normal Weight Obese Syndrome. Issue 6 (30th October 2013) - Di Renzo, L.; Sarlo, F.; Petramala, L.; Iacopino, L.; Monteleone, G.; Colica, C.; De Lorenzo, A.
Abstract : Background and Aim . Normal weight obese (NWO) syndrome is characterized by normal body mass index (BMI), but high amount of fat mass and reduced lean mass. We evaluated allelic frequency of the G/A −308 TNF- α polymorphism and prevalence of sarcopenia in NWO. Methods . We enrolled 120 Italian healthy women, distinguished into 3 groups: normal weight (NW); NWO, and preobese-obese (PreOB/OB) and evaluated anthropometric parameters, body composition by dual X-ray absorptiometry, blood tests, and genotyping of G/A −308 TNF- α polymorphism. Results . We found a positive association between sarcopenic obesity and −308 TNF- α polymorphism. All obese women were sarcopenic and were no carrier of mutation (G/G). Among all G/G, NWO showed significant differences in lean mass and total body lean mass (TBLean) with respect to NW and PreOB/OB (P < 0.001 ). Regarding appendicular skeletal muscle mass index values, 4.21% of NW were sarcopenic (50% G/G and 50% G/A); the same percentage was observed in NWO subjects (100% G/G). Moreover, 2.10% of PreOB/OB were sarcopenic and all were G/G. Conclusion . Our study suggests that TNF- α polymorphism contributes to sarcopenic obesity susceptibility, in association with body composition. This is the first study that shows the importance of TNF- α polymorphism to determine TBLean variation in NWO syndrome.